(untitled) (Interdisciplinary Studies Journal, 2021)
This article addresses the theme: The relevance of eclectic reading in the native language in Pedagogical Workshops of the More Education Program and in Complementary Activities of the Full-Time School Program as a way to foster educational improvement. The More Education Program is a government initiative created as a policy to combat poverty and social exclusion. It provides socio-educational activities during after-school hours for elementary school students, particularly in the early years. Meanwhile, the Full-Time School Program focuses on the development of public schools that fulfill their social function, enabling children and adolescents to access linguistic knowledge, engage with different types of texts, and explore transversal themes relevant to contemporary times. These themes are contextualized with the world students live in and the realities surrounding them in their municipality. Both programs are implemented in the city of São Borja, located in the western border of Rio Grande do Sul. Their aim is to provide students with a space within schools that allows continuity in their studies, ensuring that there is no interruption in pedagogical intervention. The methodology adopted will include bibliographic research and the argumentative approach proposed by Secci. The study emphasizes eclectic reading in a playful and enjoyable manner, aiming to improve language skills in public institutions. It is justified that individuals who read become critical, politicized, and active participants in society.